The Second Stage of the Rebellion Period, 1831-1836 - Sel Turhan, Fatma (I.B. Tauris & Co Ltd, 2014)
As mentioned in the previous chapter, the muhafız of Vidin, İbrahim Pașa, was appointed to the valilik of Bosnia at the end of June 1831. When İbrahim Pașa was preparing to leave Üsküb for Yenipazar on 2 September 1831, news reached him that Hüseyin Kapudan had applied to the central authorities to be awarded the valilik and was awaiting their decision.